A virtual monitoring method of operation conditions for mining and transporting equipment based on real-time data. Issue 4 (1st October 2020) - Jiao, Xiubo; Zhang, Xin; Xie, Jiacheng; Cui, Tao; Wang, Binbin; Shen, Hongda
ABSTRACT: This paper presents a virtual monitoring method of operation conditions. The mathematical calculation model of a shearer and a scraper conveyor was established. Based on the model and the real-time motion trajectory of the shearer, measuring the pitch angles of 4–6 middle troughs as a priori information, the pitch angle of the next section could be calculated by rolling, thus the shape of a scraper conveyor was obtained. The method was programmed into the bottom layer of the Unity3D software. A real-time display and updating of virtual images were realised with data visualisation driving technology. The method was verified experimentally, with the results producing an error between the calculated and actual layout forms of the scraper conveyor of less than 15 mm. The actual operation state of the equipment remains synchronised in real time with the equipment in the virtual monitoring screen. Importantly, the detection accuracy satisfies the practical requirements.